2019
DOI: 10.1021/acs.oprd.8b00446
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Crystallization of Paracetamol in a Continuous Oscillatory Baffled Reactor

Abstract: In this article, we report, for the first time, a reactive seeded cooling crystallization of paracetamol successfully performed in a continuous oscillatory baffled reactor (COBR). The synthesis of acetaminophen took place in the first part of the COBR and generated the solvent for crystallization via a specific ratio of starting materials. Seeded cooling crystallization was immediately commenced after the completion of the reaction in the second part of the COBR. We investigated the seeding strategy of three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
3
21
1
Order By: Relevance
“…The size of the single crystals remains unchanged, while the size of agglomerates increases over time. Lawton et al and Jiang et al reported the formation of smaller particles with stronger oscillation intensity, contrary to our observations where the size of single crystals does not change. The zeolite crystal size is determined by the number and distribution of nuclei in the gel matrix .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The size of the single crystals remains unchanged, while the size of agglomerates increases over time. Lawton et al and Jiang et al reported the formation of smaller particles with stronger oscillation intensity, contrary to our observations where the size of single crystals does not change. The zeolite crystal size is determined by the number and distribution of nuclei in the gel matrix .…”
Section: Resultscontrasting
confidence: 99%
“…Moreover, antisolvent and cocrystal crystallization were also assessed in COBC. More recently, Jiang et al reported for the first time reactive seeded cooling crystallization of paracetamol in a COBR at different seed content, enabling smooth, and encrustation‐free runs. These results in the field of crystallization herald that a COBR can potentially benefit the synthesis of zeolite materials from the viewpoint of handling of solid particles.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the pain points around management of secondary nucleation issues that are inherent to agitated crystallizers need to be addressed. Impeller free crystallizers such as oscillatory baffled crystallizers 39,40 and fluidic oscillators 41 pose viable technology options and need concerted efforts for further development and consistent deployment.…”
Section: Enabling Technologies For Challenging Purificationsmentioning
confidence: 99%
“…The Multistage Continuous Mixed-Suspension, Mixed-Product Removal (MSMPR) [4,[28][29][30][31][32][33], Taylor-Couette [32,34,35], or Draft Tube Baffle (DTB) [36,37] crystallizers belong to the stirred tank crystallizers. The oscillatory baffled crystallizers [32,38,39] and coiled tube crystallizers belong [40][41][42][43][44][45] to the plug flow crystallizers. Nice overviews of different crystallizer technologies are given in References [3,32,40].…”
Section: Introductionmentioning
confidence: 99%